2004
DOI: 10.1016/j.bbmt.2004.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of autologous transplantation with interleukin-2-incubated peripheral blood stem cells and posttransplantation interleukin-2 in relapsed or refractory non-Hodgkin lymphoma

Abstract: Previous work suggested that interleukin (IL)-2 can be used for eradicating residual disease in autologous grafts and for preventing recurrence. We report a phase II study of autologous peripheral blood stem cell transplantation with in vitro IL-2 incubation of peripheral blood stem cells and posttransplantation IL-2 in patients with recurrent or refractory non-Hodgkin lymphoma. Salvage chemotherapy consisted of ifosfamide and etoposide. Responding patients underwent autologous peripheral blood stem cell trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Initial trials, modeled after the regimens used for solid tumors, showed promise in patients with relapsed acute myelogenous leukemia (AML) [25,26] and lymphomas, including Hodgkin lymphoma [27][28][29][30]. Additional investigations were designed to take advantage of the unique microenvironment provided by these diseases, including the proximity of neoplastic cells to the antigen-presenting cells (APC) and immune effector cells (T and NK) in the blood and marrow [31,32]. Because the early trials in leukemia and lymphoma were encouraging, innovative strategies followed, including the combination of antibody therapy with IL-2 to enhance antibody-dependent cellular cytotoxicity and other potential synergistic interactions.…”
Section: Il-2-based Therapy Of Hematologic Malignanciesmentioning
confidence: 99%
“…Initial trials, modeled after the regimens used for solid tumors, showed promise in patients with relapsed acute myelogenous leukemia (AML) [25,26] and lymphomas, including Hodgkin lymphoma [27][28][29][30]. Additional investigations were designed to take advantage of the unique microenvironment provided by these diseases, including the proximity of neoplastic cells to the antigen-presenting cells (APC) and immune effector cells (T and NK) in the blood and marrow [31,32]. Because the early trials in leukemia and lymphoma were encouraging, innovative strategies followed, including the combination of antibody therapy with IL-2 to enhance antibody-dependent cellular cytotoxicity and other potential synergistic interactions.…”
Section: Il-2-based Therapy Of Hematologic Malignanciesmentioning
confidence: 99%
“…Despite their clear activity as phase I agents, these drugs have not been shown to have clear benefit in the post-transplant setting. A large phase II study [36] of infusion with IL-2 incubated stem cells followed by post-transplant IL-2 failed to show any benefit. Others are using more innovative approaches for post-transplant immunomodulation.…”
Section: Allogeneic Transplantationmentioning
confidence: 99%
“…Although immunostimulatory changes of potential antitumor significance were reported, these researchers did not observe beneficial effects on relapse or survival in comparison with historic controls. 24 A number of other cytokines have shown antitumor activity in lymphoma patients. One of these cytokines, IFN-a, when administered by itself or in conjunction with chemotherapy, has been shown to be effective in evoking antitumor response in 40% to 50% of the patients with low-grade NHL studied, including CR in 5% to 10% of these patients.…”
mentioning
confidence: 99%